UJI PESTISIDA NABATI SIRIH HUTAN (Piper aduncum L.) TERHADAP LARVA KUMBANG TANDUK Oryctes rhinoceros L. PADA TANAMAN KELAPA SAWIT - Joni Irawan; Rusli Rustam; Hafiz Fauzana (Jurnal Agroteknologi, 2018)
Oryctes rhinoceros is one of the main pests in oil palm crops. Such pest attacks can reduce production until 69%, even causing 25% of young plants to die. Control efforts conducted by smallholders or large companies generally use synthetic insecticides. To reduce the effects of synthetic insecticides, one of the alternatives that can be used in the technique of pest control O. rhinoceros is by the used of natural insecticides. One of the plants that can be used as a natural insecticides is piper betle forest (Piper aduncum L.).This research aims to intended to find out the ability of the extract of piper betle forest in extermination larvae O. rhinoceros of oil palm crops. The research was start since March 2017 to June 2017 at the Pest Laboratory Plants and Experiment Station Technical Implementation Unit Agriculture Faculty University of Riau. Experimentally using Completely Randomized Factorial Design (RAL) with three factor and five replications were used in the research. The first factor were S1 (Flour leaf of piper bettle), second S2 (Flour fruit of piper bettle), and S3 (Flour twig of piper bettle). Each unit of the experiment uses two methods application. The first method is application of food mixing and the second is application of watering method. The result showed that flour fruit of piper bettle with the application food mixing method and application of watering method with two method can to murder up to 92% and 80% of the larvae O. rhinoceros, with an average initial time of death of 12 hours and 28 hours. Flour fruit of piper bettle can use that effective controls of the larvae O. rhinoceros on oil palm crops because it has caused the death rate of larvae O. rhinoceros exceeds 80%.